Pengaruh Kepemimpinan dan Komunikasi Kerja terhadap Kepuasan Kerja Dosen - Putra, Arif Rachman; Sinambela, Ella Anastasya (Universitas Nusantara PGRI Kediri, 2021)
Lecturers as educators in higher education are assets that must be guaranteed to have job satisfaction based on the work results shown to the organization. This study aims to determine the significance of the influence of leadership and work communication variables on teacher performance. The number of respondents involved were 57 lecturers. The results of this study state that leadership and work communication have a significant influence on job satisfaction. Leadership is an independent variable that has a dominant influence.